Lactate dehydrogenase isoenzymes in dental pulp of rats according to stage of root development - Losso Estela Maris; Nicolau José (Fundação Odontológica de Ribeirão Preto, 2003)
The objective of this study was to present a classification of the root development stage of female rat molar teeth and to evaluate the variation in the lactate dehydrogenase (LDH) activity and electrophoretic isoenzyme profile according to the stage of root development of the molar teeth. We also studied the LDH activity and isoenzymes of the pulp of incisor teeth. The stage of development of the rat first molar at the age of 15 days and that of the second molar at the age of 18 days was classified as the beginning of root formation. At the age of 15 days, the electrophoretic profile of the isoenzymes for the first molar showed a prevalence of LDH-1 followed by LDH-2. However, for the maxillary second molar there was a prevalence of LDH-4 followed by LDH-1, while for the mandibular second molar LDH-1 predominated followed by LDH-2 and LDH-4. From 18 days of age, the prevalence was always of LDH-1. The electrophoretic profile of LDH isoenzymes from the pulp of the incisor teeth at the ages studied (25 and 60 days) showed the following order of prevalence: LDH-1 > LDH-2 > LDH-3 > LDH-4 > LDH-5. These results suggest that there are variations in the prevalence of the various forms of LDH isoenzymes in the dental pulp of rats according to the developmental stage of the root.